(untitled) - Funk, Nolan Gerard; Liboiron, Landon; 1991-; Ali, Sophia; 1995-; 1986-; Margeson, Matthew; 1980-; Albertson, Sean; 1968-; Jouffret, Jacques; 1985-; et al. (Universal City, CA, 2018)
A harmless game of truth or dare among friends turns deadly when someone, or something, begins to punish those who tell a lie or refuse the dare.
Keywords: Truth or dare (Game); Drama; Friendship; Drama; Friendship; Drama; Video recordings for the hearing impaired; Thrillers (Motion pictures); Video recordings for the hearing impaired; Pel?culas de horror; Grabaciones de v?deo para los de audici?n disminuido; Materiales en espa?ol; Biling?e.; Largometrajes; Horror films; Thrillers (Motion pictures); Fiction films; Drama; Feature films; Fiction films; Horror films; Feature films